Correlation Between Dynamic Material Behavior and Adiabatic Shear Phenomenon for Quenched and Tempered Steels - PURSCHE, F.; MEYER, L. W. (Engineering Transactions, 2011)
Besides the common failure mechanism based on crack propagation, adiabatic shear failure results from a collapse mechanism, mainly at high deformation rates. This failure incorporates locally extreme high shear strains, but due to the small volume involved, it transpires in a macroscopic brittle manner. This paper deals with the description of the influence of material properties on adiabatic shear failure. In the literature, much information can be found, which supports the theory that some material properties influence the occurrence of adiabatic shear failure behavior in a positive or negative manner. The determination of propensity for the investigated steels was done through special biaxial dynamic compression-shear-test in a drop weight tower. The failure achieved in the test is only material-dependent. Furthermore, it was found, that the theory of Culver with the competing processes of work hardening and thermal softening is transferable on the tested materials in a qualitative manner. Additionally, it was determined that few material properties have a strong controlling effect on the adiabatic shear failure behavior and it is possible to determine a critical value for transition between sheared and non sheared areas. Moreover, it could define a functional correlation of the failed materials to certain properties. As a main result, the most important material property is the dynamic compression behavior at high temperature. The stress level of the material and the characteristic in dependence of temperature is decisive. Analytical considerations using high temperature behavior patterns confirm this influence. Additionally, hardness and strength at room temperature and the pure shear capability (hat-shaped specimen) are also important for the evaluation of adiabatic failure behavior.